Use of Autochthonous Lactiplantibacillus plantarum Strains to Produce Fermented Fish Products - Speranza, Barbara; Racioppo, Angela; Campaniello, Daniela; Altieri, Clelia; Sinigaglia, Milena; Corbo, Maria Rosaria; Bevilacqua, Antonio (Frontiers in Microbiology, 2020)
The main goal of this research was the optimization of the production of a fish fermented salami-like product using autochthonous Lactiplantibacillus plantarum starters. This main topic was addressed through two intermediate steps: 1. Optimization of fermented fish product composition by using a 2k-p Fractional Factorial Design: the variables tested were nitrites (0-150 ppm), salt (2.5-7.5%), sucrose (0-4%), white pepper (0-0.10%) and fermentation temperature (10-30°C); 2. Product realization and evaluation of its microbiological profile (aerobic microflora, Pseudomonadaceae, Enterobacteriaceae and LAB populations), chemico-physical parameters (pH and aw), and sensorial quality (odour, texture, colour and overall acceptability) during its storage at 4°C for 21 days. In the first step, the fish pulp was mixed with the appropriate amounts of ingredients, according to the experimental design; each batch was individually inoculated with the studied starter (L. plantarum 11, L. plantarum 69, L. plantarum DSM1055) to a final level of 107 cfu/g and incubated at the 10, 20 or 30°C for 7 days. The lowest fermentation time (time to reach pH 4.4) was obtained with 4% sucrose, 100 ppm nitrite and a process temperature of 30°C. In the second step salami-like were produced according to the individuated formulation and inoculated with the studied starters (107 cfu/g); the fish mixture was stuffed into a natural casing and left to ferment at 30°C for 7 days. The results were promising as the use of the selected strains not only assured the correct course of fermentation but reduced the fermentation time (2 days); during refrigerated storage, a good microbiological, chemico-physical and sensorial quality of the final product was recorded for at least 21 days.